Bem-estar e estresse em estudantes da Unioeste em tempos de pandemia - Lopes, Adriana Rezende (2022)
This is a transversal and quantitative research, with the objective of knowing the mental health of UNIOESTE undergraduate students during the COVID-19 pandemic, considering the levels of symptoms of stress, anxiety, depression and academic burnout, associating them with the levels of psychological well-being, life satisfaction and/or use of strategies for stress coping, besides identifying predictors for such symptoms. We applied a questionnaire with socio-demographic, academic and health variables, and about the impact of the pandemic of COVID-19, and 5 self-applied scales validated for use in Brazil: Depression Anxiety Stress Scale - Short Form (DASS-21), Oldenburg Burnout Inventory - Student Version (OLBI-S), Psychological Well-Being (PWB), Satisfaction with Life Scale (SWLS) and BriefCOPE. Data collection occurred from September 14th to October 19th, 2020, by sending an e-mail to all undergraduate students enrolled in the 33 in-class courses at the five campuses of the university, containing an invitation to participate and a link to digitally access the survey. The convenience sample was composed of 1,224 undergraduates, being reduced in the study of academic burnout to 965 undergraduates who were in classes and filled out the respective scale. Descriptive and inferential statistics were performed (significance level α=0.05), using Spearman correlation, Pearson chi-square and Mann-Whitney tests, as well as univariate and multivariate logistic analysis. Most of the sample was female (68.6%), between 18 and 24 years old (77.9%), single (88.4%), with family income from 1 to 3 minimum wages (52.5%), in remote classes (78.1%), and not in social isolation (57, 7%), besides presenting symptoms of stress (57.5%), anxiety (52.5%) and depression (60.5%), high scores in the 6 dimensions of psychological well-being (54.6% to 98.4%) and satisfaction with life (54.9%). Study (80.6%), mental health (66.7%) and social life (65.3%) were the aspects of life reported as most negatively affected by the pandemic crisis. Stress, anxiety and depression showed common significant correlations: negative with life satisfaction, 6 dimensions of psychological well-being and 3 adaptive copings (active coping, planning and positive reinterpretation); positive with 5 maladaptive copings (behavioral disengagement, denial, self-blame, self-distraction, substance use). We found 7 common predictors for symptoms of stress, anxiety, and depression ("female sex," "age 18-24," "having chronic illness," lower scores on the self-acceptance and positive relationships with others dimensions of psychological well-being, higher use of the maladaptive copings substance abuse and selfblame). In the sample of 965 undergraduates, a high prevalence of academic burnout (76.7%), high exhaustion (83.4%) and high detachment (83.7%) were found. We found 4 predictors of academic burnout common to both females and males ("aspects of life negatively affected by the pandemic", "work beyond internship", higher use of avoidance coping, lower use of approach coping). The results indicated high prevalence of symptoms of stress, anxiety, depression and academic burnout. The findings suggest that high scores of life satisfaction, dimensions of psychological well-being and use of adaptive coping strategies may have protective effects for stress, anxiety, and depression, and the use of approach coping may have a protective effect for academic burnout.